Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Circular Economy Approach in the Utilization of Hevea brasiliensis Seed-derived Activated Carbon for Aniline Yellow Dye Adsorption - Ralph Joshua B. Onipa; Christopher N. Mapalo; John Bert T. Dimalanta; Mike Clydegil A. Laurie; Val Irvin F. Mabayo; Efren A. Pagalan (Circular Economy and Sustainability, 2026)

Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Fostering tropical cyclone research and applications with Synthetic Aperture Radar - Alexis Mouche; Arthur Avenas; Paul Chang; Bertrand Chapron; Théo Cévaër; Clément Combot; Joseph Courtney; Quentin Febvre; Ralph C. Foster; Antoine Grouazel; Masahiro Hayashi; Takeshi Horinouchi; et al. (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Rapid parameter inference with uncertainty quantification for a radiological plume source identification problem - Christopher Edwards; Ralph C. Smith (Environmental and Ecological Statistics, 2025)

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

Rapid Global Deforestation Leaves Forest‐Dependent Raptors With Half of Their Suitable Habitat Remaining - Christopher J. O'Bryan; Zunyi Xie; Hongli Li; Evan R. Buechley; Martin K.‐F. Bader; James R. Allan; Ralph Buij (Global Change Biology, 2025)
Raptors—a group that includes hawks, eagles, owls, and vultures—are among the most imperiled vertebrates, with over half of species declining and one‐fifth threatened with extinction. Most raptors depend on forests for survival, yet the extent and consequences of recent deforestation within their ranges remain poorly understood. We analyzed high‐resolution global data on forest change between 2001 and 2023 within the ranges of 369 forest‐dependent raptor species. On average, these species have lost 10% of forest within their ranges since 2001. Seventy‐seven species had already lost at least 15% of additional forest cover within their ranges in the latter half of the 20th century. Currently, only 52% of forest cover remains within forest‐dependent species' ranges on average, with many forest specialists retaining less than 25% cover. Forest‐dependent raptors listed as Critically Endangered by the IUCN have lost the most forest and now retain the least forest cover within their ranges. Shifting agriculture is the primary driver of forest loss—particularly in tropical Africa and South America—followed by commodity‐driven deforestation in Southeast Asia. Because forest loss is frequently used as a proxy for extinction risk for raptors, our findings have direct applications for species threat assessments, regional conservation priorities, and global biodiversity commitments.

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

Groundwater discharge and bank overtopping drive large carbon exports from Indian Sundarban mangroves - Douglas R. Tait; James Z. Sippo; Luke C. Jeffrey; Damien T. Maher; Abhijit Mukherjee; Christopher Ralph; Kousik Das (Science of The Total Environment, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Crossflow flat solid oxide fuel cell (SOFC) semi-empirical modeling and the multi-fuel property based on a commercial 700 W stack - Junhan Cheng; Ralph Lavery; Christopher S. McCallum; Kevin Morgan; John Doran; Chunfei Wu; Kening Sun; David W. Rooney (Fuel, 2024)

Equitable active transport - Bahar Dadashova; Ralph Buehler; Christopher Cherry; Xinyue Ye (Transportation Research Part D: Transport and Environment, 2023)

Assimilation of Blended Satellite Soil Moisture Data Products to Further Improve Noah-MP Model Skills - Jifu Yin; Xiwu Zhan; Michael Barlage; Sujay Kumar; Andrew Fox; Clement Albergel; Christopher R. Hain; Ralph R. Ferraro; Jicheng Liu (Journal of Hydrology, 2023)

Heat acclimation reduces the effects of whole-body hyperthermia on knee-extensor relaxation rate, but does not affect voluntary torque production - Ralph Joseph Frederick Hills Gordon; Jodie Natasha Moss; Federico Castelli; Thomas Reeve; Ceri Elen Diss; Christopher James Tyler; Neale Anthony Tillin (European Journal of Applied Physiology, 2023)
Purpose This study investigated the effects of acute hyperthermia and heat acclimation (HA) on maximal and rapid voluntary torque production, and their neuromuscular determinants. Methods Ten participants completed 10 days of isothermic HA (50 °C, 50% rh) and had their knee-extensor neuromuscular function assessed in normothermic and hyperthermic conditions, pre-, after 5 and after 10 days of HA. Electrically evoked twitch and octet (300 Hz) contractions were delivered at rest. Maximum voluntary torque (MVT), surface electromyography (EMG) normalised to maximal M-wave, and voluntary activation (VA) were assessed during brief maximal isometric voluntary contractions. Rate of torque development (RTD) and normalised EMG were measured during rapid voluntary contractions. Results Acute hyperthermia reduced neural drive (EMG at MVT and during rapid voluntary contractions; P < 0.05), increased evoked torques ( P < 0.05), and shortened contraction and relaxation rates ( P < 0.05). HA lowered resting rectal temperature and heart rate after 10 days ( P < 0.05), and increased sweating rate after 5 and 10 days ( P < 0.05), no differences were observed between 5 and 10 days. The hyperthermia-induced reduction in twitch half-relaxation was attenuated after 5 and 10 days of HA, but there were no other effects on neuromuscular function either in normothermic or hyperthermic conditions. Conclusion HA-induced favourable adaptations to the heat after 5 and 10 days of exposure, but there was no measurable benefit on voluntary neuromuscular function in normothermic or hyperthermic conditions. HA did reduce the hyperthermic-induced reduction in twitch half-relaxation time, which may benefit twitch force summation and thus help preserve voluntary torque in hot environmental conditions.

Barley RIC157, a potential RACB scaffold protein, is involved in susceptibility to powdery mildew - Stefan Engelhardt; Adriana Trutzenberg; Michaela Kopischke; Katja Probst; Christopher McCollum; Johanna Hofer; Ralph Hückelhoven (Plant Molecular Biology, 2023)
Key message CRIB motif-containing barley RIC157 is a novel ROP scaffold protein that interacts directly with barley RACB, promotes susceptibility to fungal penetration, and colocalizes with RACB at the haustorial neck. Abstract Successful obligate pathogens benefit from host cellular processes. For the biotrophic ascomycete fungus Blumeria hordei ( Bh ) it has been shown that barley RACB, a small monomeric G-protein (ROP, Rho of plants), is required for full susceptibility to fungal penetration. The susceptibility function of RACB probably lies in its role in cell polarity, which may be co-opted by the pathogen for invasive ingrowth of its haustorium. However, how RACB supports fungal penetration success and which other host proteins coordinate this process is incompletely understood. RIC (ROP-Interactive and CRIB-(Cdc42/Rac Interactive Binding) motif-containing) proteins are considered scaffold proteins which can interact directly with ROPs via a conserved CRIB motif. Here we describe a previously uncharacterized barley RIC protein, RIC157, which can interact directly with RACB in planta . We show that, in the presence of constitutively activated RACB, RIC157 shows a localization at the cell periphery/plasma membrane, whereas it otherwise localizes to the cytoplasm. RIC157 appears to mutually stabilize the plasma membrane localization of the activated ROP. During fungal infection, RIC157 and RACB colocalize at the penetration site, particularly at the haustorial neck. Additionally, transiently overexpressed RIC157 renders barley epidermal cells more susceptible to fungal penetration. We discuss that RIC157 may promote fungal penetration into barley epidermal cells by operating probably downstream of activated RACB.

Temperature mapping of non-photochemical quenching in Chlorella vulgaris - Andrei Herdean; Christopher Hall; David J. Hughes; Unnikrishnan Kuzhiumparambil; Bernardo Campos Diocaretz; Peter J. Ralph (Photosynthesis Research, 2023)
Light intensity and temperature independently impact all parts of the photosynthetic machinery in plants and algae. Yet to date, the vast majority of pulse amplitude modulated (PAM) chlorophyll a fluorescence measurements have been performed at well-defined light intensities, but rarely at well-defined temperatures. In this work, we show that PAM measurements performed at various temperatures produce vastly different results in the chlorophyte Chlorella vulgaris . Using a recently developed Phenoplate technique to map quantum yield of Photosystem II (Y(II)) and non-photochemical quenching (NPQ) as a function of temperature, we show that the fast-relaxing NPQ follows an inverse normal distribution with respect to temperature and appears insensitive to previous temperature acclimation. The slow-relaxing or residual NPQ after 5 minutes of dark recovery follows a normal distribution similar to Y(II) but with a peak in the higher temperature range. Surprisingly, higher slow- and fast-relaxing NPQ values were observed in high-light relative to low-light acclimated cultures. Y(II) values peaked at the adaptation temperature regardless of temperature or light acclimation. Our novel findings show the complete temperature working spectrum of Y(II) and how excess energy quenching is managed across a wide range of temperatures in the model microalgal species C. vulgaris . Finally, we draw attention to the fact that the effect of the temperature component in PAM measurements has been wildly underestimated, and results from experiments at room temperature can be misleading.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

pH variability at volcanic CO 2 seeps regulates coral calcifying fluid chemistry - Steeve Comeau; Christopher E. Cornwall; Tom Shlesinger; Mia Hoogenboom; Ralph Mana; Malcolm T. McCulloch; Riccardo Rodolfo‐Metalpa (Global Change Biology, 2022)
Coral reefs are iconic ecosystems with immense ecological, economic and cultural value, but globally their carbonate‐based skeletal construction is threatened by ocean acidification (OA). Identifying coral species that have specialised mechanisms to maintain high rates of calcification in the face of declining seawater pH is of paramount importance in predicting future species composition, and growth of coral reefs. Here, we studied multiple coral species from two distinct volcanic CO 2 seeps in Papua New Guinea to assess their capacity to control their calcifying fluid (CF) chemistry. Several coral species living under conditions of low mean seawater pH, but with either low or high variability in seawater pH, were examined and compared with those living in ‘normal’ (non‐seep) ambient seawater pH. We show that when mean seawater pH is low but highly variable, corals have a greater ability to maintain constant pH cf in their CF, but this characteristic was not linked with changes in abundance. Within less variable low pH seawater, corals with limited reductions in pH cf at the seep sites compared with controls tended to be more abundant at the seep site than at the control site. However, this finding was strongly influenced by a single species ( Montipora foliosa ), which was able to maintain complete pH cf homeostasis. Overall, although our findings indicate that there might be an association between ecological success and greater pH cf homeostasis, further research with additional species and at more sites with differing seawater pH regimes is required to solidify inferences regarding coral ecological success under future OA.

LC‐IMPACT: A regionalized life cycle damage assessment method - Francesca Verones; Stefanie Hellweg; Assumpció Antón; Ligia B. Azevedo; Abhishek Chaudhary; Nuno Cosme; Stefano Cucurachi; Laura de Baan; Yan Dong; Peter Fantke; Laura Golsteijn; Michael Hauschild; et al. (Journal of Industrial Ecology, 2020)

A Registration and Deep Learning Approach to Automated Landmark Detection for Geometric Morphometrics - Jay Devine; Jose D. Aponte; David C. Katz; Wei Liu; Lucas D. Lo Vercio; Nils D. Forkert; Ralph Marcucio; Christopher J. Percival; Benedikt Hallgrímsson (Evolutionary Biology, 2020)

An Evaluation of Neurotoxicity Following Fluoride Exposure from Gestational Through Adult Ages in Long-Evans Hooded Rats - Christopher A. McPherson; Guozhu Zhang; Richard Gilliam; Sukhdev S. Brar; Ralph Wilson; Amy Brix; Catherine Picut; G. Jean Harry (Neurotoxicity Research, 2018)

Leveraging community-based participatory research capacity to recruit Pacific Islanders into a genetics study - Pearl A. McElfish; Marie-Rachelle Narcisse; Christopher R. Long; Britni L. Ayers; Nicola L. Hawley; Nia Aitaoto; Sheldon Riklon; L. Joseph Su; Shumona Z. Ima; Ralph O. Wilmoth; Thomas K. Schulz; Susan Kadlubar (Journal of Community Genetics, 2017)

Epigenetic variation among natural populations of the South African sandhopper Talorchestia capensis - Simone Baldanzi; Ralph Watson; Christopher D. McQuaid; Gavin Gouws; Francesca Porri (Evolutionary Ecology, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

Uncertainty Management in Coupled Physical-Biological Lower Trophic Level Ocean Ecosystem Models - Ralph Milliff; Jerome Fiechter; William Leeds; Radu Herbel; Christopher Wikle; Mevin Hooten; Andrew Moore; Thomas Powell; Jeremiah Brown (Oceanography, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Two-Dimensional NMR Evidence for Cleavage of Lignin and Xylan Substituents in Wheat Straw Through Hydrothermal Pretreatment and Enzymatic Hydrolysis - Daniel J. Yelle; Prasad Kaparaju; Christopher G. Hunt; Kolby Hirth; Hoon Kim; John Ralph; Claus Felby (BioEnergy Research, 2013)

Anwendungsbeispiele für die Verwendung neuer analytischer Prüftechniken bei Hochleistungsstählen - Ralph Werl; Gerald Klösch; Waltraud Winkler; Andreas Pissenberger; Martin W. Egger; Stefan Aigner; Jürgen Pühringer; Susanne Michelic; Christian Bernhard; Wolfgang Schützenhöfer; Reinhold Schneider; Christopher Schüller (BHM Berg- und Hüttenmännische Monatshefte, 2012)

Muscle-Specific RING Finger (MuRF) cDNAs in Atlantic Salmon (Salmo salar) and Their Role as Regulators of Muscle Protein Degradation - Luca Tacchi; Ralph Bickerdike; Christopher J. Secombes; Samuel A. M. Martin (Marine Biotechnology, 2012)

Increased rate of D1 repair in coral symbionts during bleaching is insufficient to counter accelerated photo‐inactivation - Ross Hill; Christopher M. Brown; Katrina DeZeeuw; Douglas A. Campbell; Peter J. Ralph (Limnology and Oceanography, 2011)
We dissect the primary photo‐inactivation and the counteracting metabolic repair rates in fragments of the scleractinian coral, Pocillopora damicornis , subjected to a combined stress of a shift to elevated temperature (from 26°C to 32°C) and increased light (from 200 µmol photons m −2 s −1 to 400 µmol photons m −2 s −1 ) to induce bleaching. During the bleaching treatment the dinoflagellate symbionts showed a 5.5‐fold acceleration in their photosystem II (PSII) repair rate constant, demonstrating that they maintain strong metabolic capacity to clear and replace photo‐damaged D1 protein at the elevated temperature and light conditions. Nevertheless, the symbionts concurrently suffered a seven‐fold increase in the rate constant for PSII photo‐inactivation. This rapid photo‐inactivation exceeded the PSII repair capacity, therefore tipping the symbionts, and by implication the symbiosis, into net photo‐inhibition. Increased photo‐inactivation in hospite, rather than an inhibition of PSII repair, is the principle trigger for net photo‐inhibition under bleaching conditions.

Rapid photoprotection in sea‐ice diatoms from the East Antarctic pack ice - Katherina Petrou; Ross Hill; Christopher M. Brown; Douglas A. Campbell; Martina A. Doblin; Peter J. Ralph (Limnology and Oceanography, 2010)
Photoinhibition and D1 protein re‐synthesis were investigated in bottom‐dwelling sea‐ice microalgal communities from the East Antarctic pack ice during early spring. Bottom‐dwelling sea‐ice microalgal communities were dominated by diatoms that exhibited rapid photoprotection when exposed to a range of different light levels (10 µmol photons m −2 s −1 , 50 µmol photons m −2 s −1 , 100 µmol photons m −2 s −1 , and 200 µ;mol photons m −2 s −1 ). Photosynthetic capacity of photosystem II (PSII) dropped significantly over 3 h under 200 −mol photons m −2 s −1 , but largely recovered when placed in a low‐light environment (10 µmol photons m −2 s −1 ) for an additional 3 h. PSII repair rates increased with increasing irradiance, and the D1‐protein pool remained steady even under high light (200 µmol photons m −2 s −1 ). Sea‐ice diatoms showed a low intrinsic susceptibility to photoinactivation of PSII across all the light treatments, and a strong and irradiance‐dependent induction of nonphotochemical quenching, which did not depend upon chloroplast protein synthesis, was also seen. These highly plastic organisms, once thought to be adapted to shade, are in fact well equipped to withstand rapid and relatively large changes in light at low temperatures with minimal long‐term effect on their photosynthetic machinery.

Hybrid analytical and finite element numerical modeling of mass and heat transport in fractured rocks with matrix diffusion - Christopher I. McDermott; Robert Walsh; Ralph Mettier; Georg Kosakowski; Olaf Kolditz (Computational Geosciences, 2009)

Production and rooting behaviour of rolB-transgenic plants of grape rootstock ‘Richter 110’ (Vitis berlandieri × V. rupestris) - Thomas Geier; Klaus Eimert; Ralph Scherer; Christopher Nickel (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Tree Mortality in Mixed Pine–Hardwood Stands Defoliated by the European Gypsy Moth ( Lymantria dispar L.) - Mark H. Eisenbies; Christopher Davidson; James Johnson; Ralph Amateis; Kurt Gottschalk (Forest Science, 2007)
Defoliation by the European gypsy moth (Lymantria dispar L.) and subsequent tree mortality have been well documented in the northeastern United States. In this study we evaluate tree mortality after initial defoliation in mixed pine–hardwood stands in the southeastern United States as the range of European gypsy moth expands. In 1993, 46 mature pine–oak and pine–sweetgum stands were selected on the coastal plain in Maryland and Virginia along the advancing gypsy moth front. Initial stand conditions, defoliation, and tree mortality after a single defoliation outbreak were monitored for 4 years. Susceptible oaks and sweetgum were defoliated at the greatest intensities. After defoliation, mortality in attacked stands was 4.4 m2/ha higher in pine–oak stands and 1.7 m2/ha higher in pine–sweetgum stands, representing 13 and 3% of the total basal area, respectively. Mortality of pines was observed mainly among suppressed and intermediate trees. Logistic regressions were derived to correlate individual tree mortality to stand and tree factors associated with gypsy moth attack. On the basis of these models, susceptible understory species with degraded crowns in pine–oak stands were at the greatest risk of mortality. Dominant overstory pines in pine–hardwood stands appear to be at low risk.

Candidate gene database and transcript map for peach, a model species for fruit trees - Renate Horn; Anne-Claire Lecouls; Ann Callahan; Abhaya Dandekar; Lilibeth Garay; Per McCord; Werner Howad; Helen Chan; Ignazio Verde; Doreen Main; Sook Jung; Laura Georgi; et al. (Theoretical and Applied Genetics, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Comparative influence of spatial scale on beta diversity within regional assemblages of birds and butterflies - Ralph Mac Nally; Erica Fleishman; Lesley P. Bulluck; Christopher J. Betrus (Journal of Biogeography, 2004)
Aim We examined whether variation in species composition of breeding birds and resident butterflies in the Great Basin of North America depended on sampling grain (the smallest resolvable unit of study) and on the relative proximity of sampling units across the landscape. We also compared patterns between the two taxonomic groups with reference to their life‐history characteristics. Location Data for our analyses were collected from 1996 to 2003 in three adjacent mountain ranges in the central Great Basin (Lander and Nye counties, Nevada, USA): the Shoshone Mountains, Toiyabe Range and Toquima Range. Methods Data on species composition for both taxonomic groups were collecting using standard inventory methods for birds and butterflies in temperate regions. Data were compiled at three sampling grains, sites (average 12 ha), canyons (average 74 ha) and mountain ranges. For each sampling grain in turn, we calculated similarity of species composition using the Jaccard index. First, we investigated whether mean similarity of species composition among the three ranges differed as a function of the grain size at which data were compiled. Secondly, we explored whether mean similarity of species composition was greater for canyons within the same mountain range than for canyons within different mountain ranges. Thirdly, we examined whether mean similarity of species composition at the site level was different for sites within the same canyon, sites within different canyons in the same mountain range, and sites within canyons in different mountain ranges. We used a Bayesian model to analyse these comparisons. Results For both taxonomic groups, mean similarity of species composition increased as the sampling grain increased. The effect of spatial grain was somewhat greater for birds than for butterflies, especially when the intermediate sampling grain was compared with the smallest sampling grain. Similarity of species composition of butterflies at each sampling grain was greater than similarity of species composition of birds at the same grain. Mean similarity of species composition of both birds and butterflies at the canyon level and site level was affected by relative proximity of sampling locations; beta diversity increased as the relative isolation of sampling locations increased. Main conclusions The sensitivity of beta diversity to sampling grain likely reflects the effect of local environmental heterogeneity: as sampling grain increases, biotic assemblages appear more homogeneous. Although breeding birds in our study system have larger home ranges than resident butterflies, birds may have more specialized resource requirements related to vegetation structure and composition, especially at small sampling scales. The degree of variation in species composition of both taxonomic groups suggests that spatially extensive sampling will be more effective for drawing inferences about regional patterns of species diversity than intensive sampling at relatively few, smaller sites.

Hierarchical Partitioning Public-domain Software - Ralph Mac Nally; Christopher J. Walsh (Biodiversity and Conservation, 2004)

Nestedness analysis and conservation planning: the importance of place, environment, and life history across taxonomic groups - Erica Fleishman; Christopher J. Betrus; Robert B. Blair; Ralph Mac Nally; Dennis D. Murphy (Oecologia, 2002)

The genes ABI1 and ABI2 are involved in abscisic acid- and drought-inducible expression of the Daucus carota L. Dc3 promoter in guard cells of transgenic Arabidopsis thaliana (L.) Heynh. - Regina K. F. Chak; Terry L. Thomas; Ralph S. Quatrano; Christopher D. Rock (Planta, 2000)